Warming and Salt Intrusion Affect Microcystin Production in Tropical Bloom-Forming Microcystis - Bui Trung; Marlies E. Vollebregt; Miquel Lürling (Toxins, 2022)
The Vietnamese Mekong Delta is predicted to be one of the regions most impacted by climate change, causing increased temperature and salinity in inland waters. We hypothesized that the increase in temperature and salinity may impact the microcystin (MC) production of two Microcystis strains isolated in this region from a freshwater pond (strain MBC) and a brackish water pond (strain MTV). The Microcystis strains were grown at low (27 °C), medium (31 °C), high (35 °C) and extremely high (37 °C) temperature in flat photobioreactors (Algaemist). At each temperature, when cultures reached a stable state, sea salt was added to increase salinity to 4‰, 8‰, 12‰ and 16‰. MC concentrations and cell quota were reduced at high and extremely high temperatures. Salinity, in general, had comparable effects on MC concentrations and quota. At a salinity of 4‰ and 8‰, concentrations of MC per mL of culture and MC cell quota (based on chlorophyll, dry-weight and particle counts) were higher than at 0.5‰, while at the highest salinities (12‰ and 16‰) these were strongly reduced. Strain MBC produced five MC variants of which MC-RR and MC-LR were most abundant, followed by MC-YR and relatively low amounts of demethylated variants dmMC-RR and dmMC-LR. In strain MTV, MC-RR was most abundant, with traces of MC-YR and dmMC-RR only in cultures grown at 16‰ salinity. Overall, higher temperature led to lower MC concentrations and cell quota, low salinity seemed to promote MC production and high salinity reduced MC production. Hence, increased temperature and higher salinity could lead to less toxic Microcystis, but since these conditions might favour Microcystis over other competitors, the overall biomass gain could offset a lower toxicity.